2013
DOI: 10.1111/jdv.12331
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term study of infliximab for psoriasis in daily practice: drug survival depends on combined treatment, obesity and infusion reactions

Abstract: This retrospective review of a cohort of patients with moderate-to-severe psoriasis treated with infliximab in daily practice shows that the PASI75 response rates at 24 and 52 weeks of treatment are similar to those of the pivotal studies, but 37 courses of treatment (59%) had to be discontinued after a median of 12 months. The major cause for discontinuation was loss of response, in 18 cases. Combination treatment, obesity and infusion reactions were found to be predictors of drug survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
21
1
8

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 27 publications
7
21
1
8
Order By: Relevance
“…In agreement with other studies with biologic therapies, PASI 75 response attainment was not found to be associated with smoking status, alcohol consumption and age at disease onset, although smoking at initiation of anti‐TNFα therapy has been reported as a predictor of non‐response elsewhere . The only identified negative predictor of PASI 75 response attainment was the presence of comorbidities, supported by reports linking high comorbidity burden with psoriasis disease severity as well as with treatment failure with biologics …”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…In agreement with other studies with biologic therapies, PASI 75 response attainment was not found to be associated with smoking status, alcohol consumption and age at disease onset, although smoking at initiation of anti‐TNFα therapy has been reported as a predictor of non‐response elsewhere . The only identified negative predictor of PASI 75 response attainment was the presence of comorbidities, supported by reports linking high comorbidity burden with psoriasis disease severity as well as with treatment failure with biologics …”
Section: Discussionsupporting
confidence: 88%
“…Notably, the mean baseline PASI (22.4 vs. 23.4 herein) and median baseline BMI (27.9 vs. 28.6 kg/m 2 herein) were comparable between the two studies, with the proportion of obese patients only slightly higher in the present study (37.5% vs. 40.4%). Similarly to the results of our study, baseline obesity was not found to be associated with infliximab's response attainment rates in the retrospective study conducted in Spain . Yet, several other studies have reported high BMI to be a negative predictor of response to biologics (including infliximab) .…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The safety profiles of IFX treatment in patients with rheumatic diseases has been verified by registries in many countries . However, only a few studies including several hundreds of psoriasis patients reported about the safety and efficacy of IFX treatment in real‐world clinical practice …”
Section: Discussionsupporting
confidence: 61%
“…Clinical outcomes (mainly PASI) were reported in 75% of prospective studies [27, 39, 47-53], in about 50% of prospective registries [20, 24, 54-61] and retrospective studies [29, 30, 32, 34, 37, 62-70], and in no retrospective administrative databases/claims. Drug survival of biological therapies was reported in over 60% of prospective registries [14, 20, 21, 24, 25, 31, 54, 57, 71-74], retrospective studies [18, 19, 22, 23, 26, 29, 30, 32, 34, 37, 38, 68, 70, 75-77] and administrative databases/claims [28, 35, 36, 40-42, 46], and less frequently (33%) in prospective studies [27, 33, 52, 78]. Subanalyses on reasons of discontinuation, such as switching, dose augmentation, or biological therapy restarting, were scanty.…”
Section: Resultsmentioning
confidence: 99%